Análise de riscos em uma planta industrial de produção de poliuretano: aplicação da metodologia HAZOP - Rocco, Victor Capodaglio (Universidade Federal de São Carlos, 2025)
The polyurethane production process, despite being well known and carried out for a long time and consisting of few steps, it is still a difficult process to control due to the nature of its formation reaction; and it presents significant risks, both of significant material damage and of harm to the lives of exposed people. In view of this scenario, a risk analysis for an industrial production plant of such a product is essential to identify, evaluate and control the hazards of this activity in order to protect the integrity of workers and production facilities. Based on this, this study aims to identify possible failure scenarios or deviations from the desired conditions that may compromise the safety of the process using the HAZOP (Hazard and Operability Study) analysis methodology, and thus propose effective measures to mitigate and control the identified risks. As a result of this study, 5 critical and 9 severe scenarios were identified, totaling 54% of the scenarios analyzed, all of them having suggestions on how to mitigate those risks. This made clear the importance of safety analysis for the development of this process and the complexity of a complete analysis for the satisfactory safety of an installation of this type.
Risk analysis in a polyurethane production plant: application of the HAZOP methodology
Keywords: Produção de poliuretano; Análise de riscos; Hazard and Operability Study (HAZOP); Mitigação e controle de riscos; Polyurethane production; Risk analysis; Risk mitigation and control; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura; 8. Trabalho Decente e Crescimento Econômico; 3. Saúde e Bem-Estar